Study on the Relation of Structure and Antioxidant Activity of Isorhamnetin, Quercetin, Phloretin, Silybin and Phloretin Isonicotinyl Hydrazone - Zuo, Airen; Yu, Yanying; Li, Jing; Xu, Binbin; Yu, Xiongying; Qiu, Yan; Cao, Shuwen (Free Radicals and Antioxidants, 2020)
Background: Some flavonoids compounds from the Chinese Traditional Medicine such as isorhamnetin, quercetin, phloretin, silybin have excellent antioxidant activity. Phloretin isonicotinyl hydrazone which was a new compound synthesized by our team, was expected to have more antioxidant activity than phloretin. Materials and Methods: The experiment examined the scavening free radicals activity and inhibition of lipid peroxidation activity of quercetin, isorhamnetin, phloretin, silybin and phloretin isonicotinyl hydrazone, with the methods including scavening1,1-diphenyl-2-picrylhydrazyl(DPPH) radical,2,2-azino-bis-(3-ethylbenzthiazoline-6-sulfonic acid (ABTS) radical and inhibition of Sprague Dawley (SD) rats liver mitochondria lipid peroxidation induced by Fe2+ / Vc system in vitro. Results: The experiment results showed that the five flavonoids had excellent antioxidant activity with the suitable concentration. In the experiment of scavening DPPH, ABTS radicals and inhibiting lipid peroxidation, the IC50 of isorhamnetin was respectively 24.61μmol/L,14.54μmol/L, 6.67μmol/L. The IC50 of quercetin was respectively 3.07μmol/L, 3.64μmol/L, 6.67μmol/L. The IC50 of phloretin was respectively 7.69μmol/L, 4.54μmol/L, 12.50μmol/L. The IC50 of phloretin isonicotinyl hydrazone was respectively 1.92 μmol/L, 2.27μmol/L, 2.08μmol/L. The IC50 of silybin was respectively 96.15μmol/L, 7.10μmol/L,104.16μmol/L. Conclusion: The experiment results showed that quercetin, isorhamnetin, phloretin, silybin and phloretin isonicotinyl hydrazone had excellent antioxidant activity. This was the first time to study the antioxidant activity of phloretin isonicotinyl hydrazone. Moreover, for isorhamnetin, quercetin, phloretin, silybin, this was the first time to study the activity of inhibition of SD rats liver mitochondria lipid peroxidation induced by Fe2+ / Vc system in vitro. In a word, the results of experiments showed that the molecular had more phenolic hydroxyl groups, the ability of scavenging DPPH, ABTS radicals free radical was stronger. While phloretin isonicotinyl hydrazone which was added a hydrazone group, increased the ability of scavenging DPPH, ABTS free radical and inhibiting lipid peroxidation than phloretin. Quercetin is the typical structure flavonoid, phloretin is the two-hydrogen-chalcone flavonoid with the open loop structure after hydrogenation. Silybin is the lignan flavonoid compound which has the ABCDE five rings, the structure is much more complicated. The different molecular structures of quercetin , phloretin and silybin lead to the different antioxidant activity.